2014
DOI: 10.1373/clinchem.2013.212993
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Immunoassay for the Kidney-Specific Protein myo-Inositol Oxygenase, a Potential Biomarker of Acute Kidney Injury

Abstract: Background Acute kidney injury (AKI) affects 45% of critically ill patients resulting in increased morbidity and mortality. The diagnostic standard, serum creatinine (SCr), is non-specific and may not increase until days after injury. There is significant need for a renal specific AKI biomarker detectable early enough that there would be a potential window for therapeutic intervention. In this study, we sought to identify a renal specific biomarker of AKI. Methods Gene expression data was analyzed from norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 39 publications
(40 reference statements)
1
28
0
Order By: Relevance
“…Current researches have shown that MIOX not only regulates MI metabolism but also participates in the pathogenesis of DN tubular injury through non-MI metabolic pathways, such as by stimulating the release of TGF β [15], disrupting the redox status [16] and regulating mitochondrial dynamics [17]. Interestingly, Gaut et al found that an increase in serum MIOX preceded the elevation of serum creatinine in patients with acute kidney injury (AKI), which was closely associated with the degree of tubular damage [18], indicating that serum MIOX can be used as an AKI biomarker. Despite the evident importance of MIOX in streptozotocin-induced diabetic mice tubular injury, little is known about its role and diagnostic value in DN patients.…”
Section: Introductionmentioning
confidence: 99%
“…Current researches have shown that MIOX not only regulates MI metabolism but also participates in the pathogenesis of DN tubular injury through non-MI metabolic pathways, such as by stimulating the release of TGF β [15], disrupting the redox status [16] and regulating mitochondrial dynamics [17]. Interestingly, Gaut et al found that an increase in serum MIOX preceded the elevation of serum creatinine in patients with acute kidney injury (AKI), which was closely associated with the degree of tubular damage [18], indicating that serum MIOX can be used as an AKI biomarker. Despite the evident importance of MIOX in streptozotocin-induced diabetic mice tubular injury, little is known about its role and diagnostic value in DN patients.…”
Section: Introductionmentioning
confidence: 99%
“…New studies are carried out to search more specific new markers in AKI diagnosis, serum creatinine falling short to meet the criterion of being a specific marker prior to full blown AKI (7). Despite the fact that NGAL, KIM-1, IL-18, IGFBP7, liver-type fatty acid-binding protein 1 and N-acetyl-β-D-glucosaminidase are relevant in the diagnose of AKI, these parameters were not used routinely to show AKI because of difficulties related to reliability and accuracy in the measurement methods (7,(10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…It takes many days to rise until the loss of ca. 50% of glomerular functions (6,7). It is, therefore, inevitable to search new markers pinpointing a possible AKI in advance (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Clinical Chemistry, Gaut and colleagues report on a potential novel structural biomarker of AKI, myo-inositol oxygenase (MIOX) (14 ). These researchers used an innovative approach to discover a kidney-specific protein that could be released from PTECs during AKI.…”
Section: Acute Kidney Injury (Aki)mentioning
confidence: 99%